Computer and Web Application Training for Saren Village Officers, Kalijambe Distric, Sragen - Hernawan Sulistyanto; N Nurgiyatna (Urecol Journal. Part F: Community Development, 2021)
This community service activity aims at providing motivation, knowledge, and skills/expertise in computer and information technology to improve the skills and competencies of village officials in serving the community. The participants are village officials in Saren Village, Kalijambe, Sragen, Central Java. This service activity includes several methods, namely lectures, demonstrations, exercises, and questions and answers. The lecture method activates the spirit to increase the learning motivation of the participants as well as to explain the concept of computer technology. The demonstration method demonstrates a work and learning process, namely the stages of operating a computer application. Meanwhile, the practice method practices how to assemble and run some of the applications learned. The question-and-answer provides for consulting the obstacles that arise during the training and learning process. Finally, the conclusion is all of the training participants were very enthusiastic about the computer application training activities which were held with indications that the participants (village officers) after the training ended were able to understand all the material presented and practice it well. One obstacle that arises during activity is limited computer equipment leads to the implementation of training activities not being able to run optimally.